Imam Al-Kisa'i's Qira'at Contribution for Qur'anic Interpretation - Safitri, Lidia Nur Eka; Ulya, Erviana Iradah (Al-Karim: International Journal of Quranic and Islamic Studies, 2023)
The differences in qira'at al-Qur'an have become a primary object of debate if they are not understood thoroughly. This is because these differences have been present since the Prophet Muhammad lived. Sourced from the Prophet, Muhammad then narrated by the companions to the tabi'in and continued to the Muslims from generation to generation. The inevitable difference does not symbolize the inconsistency of the Qur'anic verse, but on the contrary, is the elasticity of the Qur'anic text in response to differences in the lahjah of the Arab tribes. Thus, no one tries to unite the recitation of the Qur'an in one qirā'at. Even these differences are accepted, with a tolerant and airy attitude. This was later reviewed by the Imams of qirā'at who highlighted the differences in qirā'atqirā'at. One of these is Imam Al-Kisa'i. Imam Al-Kisa'i was one of the imams of qirā'at sab'ah who came from Kufa. Even though Al-Kisa'i has a mutawatir sanad of knowledge, he does not avoid being selective about his teacher's reading. The author used qualitative research. The result of his research is that the differences in qira'at brought by Imam Al-Kisa'i all do not have differences in meaning that deviate from the real meaning of the verse. Examples found in several verses of the Qur'an include: QS (2):144, QS (2):208, QS (2):222, QS (3):19, QS (3):161, QS (3):195, QS (5):45, QS (4):19, QS (5):112, QS (6):159, QS (11):46, QS (74):5, QS (6):111, QS (33):33. Contribution: This study affirms the flexibility of Qur'anic qira'at, the role of Imam Al-Kisa'i, and the importance of tolerance in recitation differences.